Interpersonal Synchrony in the Context of Caregiver-Child Interactions: A Document Co-citation Analysis - Carollo, Alessandro; Lim, Mengyu; Aryadoust, Vahid; Esposito, Gianluca (Frontiers in Psychology, 2021)
Social interactions accompany individuals throughout their whole lives. When examining the underlying mechanisms of social processes, dynamics of synchrony, coordination or attunement emerge between individuals at multiple levels. To identify the impactful publications that studied such mechanisms and establishing the trends that dynamically originated the available literature, the current study adopted a scientometric approach. A sample of 543 documents dated from 1971 to 2021 was derived from Scopus. Subsequently, a document co-citation analysis was conducted on 29,183 cited references to examine the patterns of co-citation among the documents. The resulting network consisted of 1,759 documents connected to each other by 5,011 links. Within the network, five major clusters were identified. The analysis of the content of the three major clusters - namely, "Behavioral synchrony", "Towards bio-behavioral synchrony", and "Neural attunement" - suggests an interest in studying attunement in social interactions at multiple levels of analysis, from behavioral synchrony to neural attunement, by passing through the level of physiological coordination. Furthermore, although initial studies on synchrony focused mostly on parent-child interactions, new hyperscanning paradigms are allowing researchers to explore the role of biobehavioral synchrony in all social processes in a real-time and ecological fashion. Future potential pathways of research were also discussed.